2017
DOI: 10.3390/ijerph14070723
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of TPOAb and TGAb with Risk of Thyroid Nodules: A Large Epidemiological Study

Abstract: Objective: The association between thyroid hormones, thyroid autoantibodies, and thyroid nodules are still not clear. The cross-sectional study, conducted in Hangzhou, China in 2010, aimed to identify the relationship of thyroid hormones and autoantibodies with thyroid nodules. Methods: Information regarding social demography was collected by a questionnaire. Thyroid hormones (triiodothyronine, thyroxin, free triiodothyronine, free thyroxin, thyrotropin), thyroid autoantibodies (thyroid peroxidase antibody, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…TPOAb positivity is also associated with other pregnancy complications, such as preterm birth [3]. In the broader context it is worth adding that thyroid antibodies, i.e., TPOAb and TgAb, were positively associated with the risk of thyroid nodules [20].…”
Section: Discussionmentioning
confidence: 99%
“…TPOAb positivity is also associated with other pregnancy complications, such as preterm birth [3]. In the broader context it is worth adding that thyroid antibodies, i.e., TPOAb and TgAb, were positively associated with the risk of thyroid nodules [20].…”
Section: Discussionmentioning
confidence: 99%
“…yroid nodules are one or more lumps made up of abnormal clusters of thyroid cells in the thyroid gland with a variety of etiologies, which can be cystic, solid, or mixed, and are the most common thyroid diseases in clinical settings [1,2]. yroid nodules can be complicated by various thyroid diseases because of its insidious onset, and most of the patients are asymptomatic in the early stage [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…yroid nodules can be complicated by various thyroid diseases because of its insidious onset, and most of the patients are asymptomatic in the early stage [3,4]. e prevalence of thyroid nodules among males and females was 29.49% and 33.15% in Southeast China, respectively [2]. With lifestyle and dietary changes, diabetes, hypertension, metabolic diseases such as hyperlipidemia, fatty liver, hyperuricemia, and obesity are the main chronic diseases affecting the health of residents in China [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study of 31 provinces in mainland China showed that the positive rate of anti-TPO antibodies (TPOAb) in Chinese adults was 10.19%, and the positive rate of anti-Tg antibodies (TgAb) was 9.70% [2]. Recent studies have con rmed that TgAb and TPOAb can increase the risk of thyroid cancer and thyroid nodules [3,4]. High levels of thyroid antibodies not only cause hypothyroidism but are also an essential factor in the progression of HT disease.…”
Section: Introductionmentioning
confidence: 99%